Accelerating Classroom Attending Behaviors and Learning Rate. Section Two. Interim Report - Walken, Christine L.; Oregon Univ., Eugene ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
Special schools or special classes are the prevalent vehicles of deviant behavior modification, although it is proposed here that effort should be first made to determine variables which influence behavior development and disturbance in the regular classroom. A need is seen to develop methods useful in regular classrooms to prevent or intervene in the development of behavior disorders. The present study evaluates the effects of token reinforcement, programed instruction, and Hawthorne-type social reinforcement, on the attending behavior and learning rates of behaviorally disruptive fourth-grade boys. Compared with a control group were four groups of boys. Token reinforcement in combination with programed learning was more effective than either treatment alone, or the Hawthorne effects treatment. Limitations are discussed in extending the methods or results to regular classroom use. (BP)
Contract Number: OEG-4-6-061308-0571.
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Bureau of Research.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Behavior Development; Behavior Problems; Classroom Techniques; Elementary School Students; Antisocial Behavior; Behavior Change; Change Agents; Programed Instruction; Reinforcement